Epidemiological aspects of witches broom disease of cupuassu tree in the microregion of Belém, PA, Brazil - Benchimol, Ruth Linda; Albuquerque, Fernando Carneiro de; Nascimento, Risaldo Muniz do (Pesquisa Agropecuaria Brasileira, 2001)
A field experiment was set at Embrapa-Centro de Pesquisa Agropecuária do Trópico Úmido, in Belém, PA (1°28' S; 48°27' W), from June/91 to May/94, aiming to follow vegetative brooms caused by Crinipellis perniciosa ((Stahel) Singer), produced in seven-year-old cupuassu trees (Theobroma grandiflorum (Willd. ex Spreng.) K. Schum.), from emission to basidiocarp production. Correlation coefficients between epidemiological variables (number of vegetative brooms, green and drying period, latent period, basidiocarp production) and climatic variables (maximum relative humidity of the air, sunshine, rainfall) were determined. The emission of vegetative brooms was observed mostly in July and August. Brooms remained green for 34.9 to 65.2 days and dried after 5.8 to 10 days. After emission, vegetative brooms delayed from 79.5 to 347 days to begin basidiocarp production, which occurred mostly from May on, with the peak in June. The correlations between the climatic variables, maximum relative humidity of air and sunshine were significant only for basidiocarp production, with negative and positive effects, respectively.